Pengaruh Insentif dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Bagian Office PT. Skinsol Kosmetik Industri - Saripah, Siti; Priyani, Ismaya Dwi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine the effect of incentives and work environment on employee performance in the Office section of PT Skinsol Cosmetics Industry. The population in this study were all employees of PT Skinsol Cosmetics Industry totaling 400 people. The sample used was the office section population totaling 50 people. The research method used in this study is a quantitative approach. As an initial step, the author collected data related to the topic being studied through books that were used as reference sources to obtain theoretical foundations and data analysis methods. The next step involves a research approach by examining a particular subject, where the conclusions produced only apply to that subject. From the results of the study entitled